A genetic manipulation of motor neuron excitability does not alter locomotor output in Drosophila larvae - McKiernan,Erin C. (PeerJ PrePrints, 2015)
Are motor neurons just passive relayers of the signals they receive? Or, do motor neurons shape the signals before passing them on to the muscles, thereby influencing the timing of motor behavior? Few direct tests of the role of motor neuron intrinsic properties in shaping motor behavior have been carried out, and many questions remain about the role of specific ion channel genes in motor neuron function. In this study, two potassium channel transgenes were expressed in Drosophila larval motor neurons to increase their excitability. Mosaic animals were created in which some identified motor neurons expressed the transgenes while others did not. Motor output underlying crawling was compared in muscles innervated by control and experimental neurons in the same animals. Counterintuitively, no effect of the transgenic manipulation on motor output was seen. Future experiments are outlined to determine how the larval nervous system produces normal motor output in the face of altered motor neuron excitability.
Keywords: ion channels; motor neurons; motor pattern; locomotion; excitability; intrinsic properties; drosophila; eag; shaker; EKI